2003
DOI: 10.1097/00004850-200301000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol for the treatment of aggressive behaviour in patients with dementia

Abstract: Aggressive behaviour is commonly observed in patients with dementia, and current pharmacological treatments are still deficient in terms of efficacy and tolerability. Allopurinol is an inhibitor of the enzyme xanthine oxidase, with previously suggested anti-aggressive effects. After successful treatment of aggression in two patients, we performed a case-series study with allopurinol 300 mg a day orally for 6 weeks (increasing 300 mg every 2 weeks if the response was less than 50%) in six patients with dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…They suggested that a dysfunction inpurinergic systemwould result in reduced adenosinergic activity as a possible common explanation for the imbalance between dopaminergic and glutamatergic neurotransmission and the dysregulation of neuro-immunological interaction that are characteristic hallmarks of schizophrenia (Lara et al, 2006; Lara and Souza, 2000). The hypothesis was largely based on preliminarydata suggesting a beneficial therapeutic activity of the purine derivative allopurinol in patients with schizophrenia and a moderateefficacy against aggressive behaviour(Lara et al, 2000; Lara et al, 2001; Lara et al, 2003). Next, we will review the support for the adenosine hypothesis of schizophrenia by highlighting adenosine's interactions with dopaminergic and glutamatergic neurotransmission, as well as its possible roles in the neurodevelopmental aspects of disease aetiology.…”
Section: The Adenosine Hypothesis Of Schizophreniamentioning
confidence: 99%
“…They suggested that a dysfunction inpurinergic systemwould result in reduced adenosinergic activity as a possible common explanation for the imbalance between dopaminergic and glutamatergic neurotransmission and the dysregulation of neuro-immunological interaction that are characteristic hallmarks of schizophrenia (Lara et al, 2006; Lara and Souza, 2000). The hypothesis was largely based on preliminarydata suggesting a beneficial therapeutic activity of the purine derivative allopurinol in patients with schizophrenia and a moderateefficacy against aggressive behaviour(Lara et al, 2000; Lara et al, 2001; Lara et al, 2003). Next, we will review the support for the adenosine hypothesis of schizophrenia by highlighting adenosine's interactions with dopaminergic and glutamatergic neurotransmission, as well as its possible roles in the neurodevelopmental aspects of disease aetiology.…”
Section: The Adenosine Hypothesis Of Schizophreniamentioning
confidence: 99%
“…[15] Allopurinol has likewise been found helpful in the treatment of aggressive behavior in patients with dementia in a case-series study. [16] Although this antioxidant activity of allopurinol has received little attention in dermatology, it may have potential application for the treatment of skin diseases.…”
Section: Mechanism Of Action Of Allopurinolmentioning
confidence: 99%
“…For example, we have demonstrated that allopurinol, a xanthine oxidase inhibitor, was an effective and well-tolerated adjuvant treatment for poorly responsive schizophrenia, refractory aggressive behavior and mania [125][126][127][128][129]. These results were confirmed by an independent group [130,131] and are hypothesized to be due to an indirect increase in extracellular purine levels (adenosine and guanosine) [12].…”
Section: Discussionmentioning
confidence: 83%